Risk Factors for Invasive Meningococcal Disease Belonging to a Novel Urethritis Clade of Neisseria meningitidis—United States, 2013–2017. (25th January 2022) - Oliver, Sara E; Retchless, Adam C; Blain, Amy E; McNamara, Lucy A; Ahrabifard, Susann; Farley, Monica; Weiss, Don; Zaremski, Elizabeth; Wang, Xin; Hariri, Susan
Abstract: We describe cases of invasive meningococcal disease caused by nongroupable Neisseria meningitidis belonging to a novel phylogenetic clade associated with urethritis. Seven cases were identified, comprising 0.6% of sequenced invasive meningococcal disease isolates from 2013 to 2017. Five patients had a known or likely immunocompromising condition, including 2 with a complement deficiency.